Dropping out of higher education: Analysis of variables that characterise students who interrupt their studies - María Olga González-Morales; David López-Aguilar; Pedro Ricardo Álvarez-Pérez; Pedro Antonio Toledo-Delgado (Acta Psychologica)
One of the persistent problems faced by the university education system is the dropout rate. The main aim of this research was to identify the profile characteristics of those students who drop out of their studies, seeking in-depth knowledge of the reality behind the issue. The responses to a questionnaire of 149,837 students from three Spanish universities (La Laguna, Zaragoza and Huelva) who had dropped out of their undergraduate studies were analysed. The outcomes enabled us to identify a number of features associated with the likelihood of dropping out of university studies. Specifically, it was found that the university of study, sex, age, study branch, entry qualification, scholarship or grant, nationality and job are predictors of dropout. The results obtained have an important transfer value, with a view to implementing actions for the adaptation of students and to avoid university dropout.